Transradial carotid artery stenting using double layer micromesh stent and novel post-dilation balloon with integrated embolic protection - Petkoska Spirova, Danica; Zafirovska, Biljana; Vasilev, Ivan; Saylors, Elizabeth; Sachar, Ravish; Kedev, Sashko (Elsevier BV, 2024)
The highest rate of embolization during carotid artery stenting occurs during post-dilation. We evaluated the ability of the Paladin system (Contego Medical, Raleigh, NC), a novel PTA balloon with an integrated 40-ɥm pore filter, to collect microemboli that may pass into the cerebral circulation when used during post-dilation.